2020
DOI: 10.3390/su12219166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Operators in Safety Perception of AV Deployment—Insights from a Large European Survey

Abstract: Autonomous vehicles are anticipated to play an important role on future mobility offering encouraging solutions to today’s transport problems. However, concerns of the public, which can affect the AVs’ uptake, are yet to be addressed. This study presents relevant findings of an online survey in eight European countries. First, 1639 responses were collected in Spring 2020 on people’s commute, preferred transport mode, willingness to use AVs and demographic details. Data was analyzed for the entire dataset and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
(67 reference statements)
3
18
0
1
Order By: Relevance
“…Nazari et al [56] found that young males are more likely to switch to AV compared to conventional vehicles, whereas older users are more likely to switch to SAV, although Laidlaw [57] concluded that young adults are more willing to pay for an AV and to use an SAV. Moreover, household car availability is a crucial factor, since Menon et al [58] found that although single-car households may replace the sole car with an SAV service, multiple-car households may only dispose of one of their cars with an SAV service. However, age and car use are directly linked with each other, since younger and elderly travellers show lower levels of driving licence holding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nazari et al [56] found that young males are more likely to switch to AV compared to conventional vehicles, whereas older users are more likely to switch to SAV, although Laidlaw [57] concluded that young adults are more willing to pay for an AV and to use an SAV. Moreover, household car availability is a crucial factor, since Menon et al [58] found that although single-car households may replace the sole car with an SAV service, multiple-car households may only dispose of one of their cars with an SAV service. However, age and car use are directly linked with each other, since younger and elderly travellers show lower levels of driving licence holding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An elderly driver using his or her car only for short shopping trips might not see this new technology as necessary as being as someone with high mileage in various conditions. Since it can be expected that income is related to willingness to pay for ADS (Kyriakidis et al, 2020 ; Zandieh and Acheampong, 2021 ), in this study, the cost of ADAS and ADS features were defined as “cost-free” in order to eliminate the effect of socio-economic background. While this constraint might be theoretically sound, it is still possible that the cost of new technology plays a role in preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also found that younger drivers were more interested in using self-driving technology and that younger drivers were prepared to pay more for this technology than older drivers (Kyriakidis et al, 2015 ; Bansal et al, 2016 ; Hohenberger et al, 2016 ). A recent survey conducted in eight European countries showed that the elderly are concerned mostly about the safety of automated driverless vehicles and would prefer to travel in autonomous vehicles with the presence of a human supervisor (Kyriakidis et al, 2020 ). Similar findings showing that older and disabled persons are more concerned about reliability and safety of the autonomous vehicles, than younger and non-disabled persons, have been found in several earlier studies (Nielsen and Haustein, 2018 ; Gabrhel et al, 2019 ; Huff et al, 2019 ; Liu et al, 2019 ; Robertson et al, 2019 ; Liang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spurningalistanum var dreift hérlendis til félagsmanna Verkfraeðingafélags Íslands, starfsfólks Vegagerðarinnar, starfsfólks Skipulagsstofnunar, starfsfólks og nemenda Háskóla Íslands, starfsfólks og nemenda Landbúnaðarháskóla Íslands, aðildarfyrirtaekja Bílgreinasambandsins og fleiri aðila auk persónulegra tengiliða höfunda skv Thomopoulos et al (2020)…”
unclassified